1998
DOI: 10.1063/1.122732
|View full text |Cite
|
Sign up to set email alerts
|

Structure and hydrogen content of stable hot-wire-deposited amorphous silicon

Abstract: Thin-film transistors incorporating a hot-wire chemical-vapor-deposited silicon layer have been shown to exhibit superior electronic stability as compared to glow-discharge-deposited amorphous silicon devices. Hot-wire-deposited silicon films of various thicknesses (37–370 nm) on silicon dioxide were investigated. The films are structurally inhomogeneous. Raman measurements and transmission electron microscopy show that isolated cone-shaped crystals grow within a primarily amorphous layer. The amorphous interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Also, the hydrogen concentration in this material was shown to be low, at 2 at. %, 15 which indicates that the mobility gap will be smaller than that of conventional a-Si:H. With this in mind, we put forward the following explanation for the occurrence of the inverse MNR in some of our intrinsic het-Si devices. The explanation is based on the band alignment of the constituent phases of nanocrystalline domains embedded in an amorphous matrix, and is derived from the model given by Lucovsky and Overhof that described and explained the inverse MNR in heavily doped microcrystalline silicon.…”
Section: H Meiling A) and R E I Schropp B)mentioning
confidence: 82%
See 1 more Smart Citation
“…Also, the hydrogen concentration in this material was shown to be low, at 2 at. %, 15 which indicates that the mobility gap will be smaller than that of conventional a-Si:H. With this in mind, we put forward the following explanation for the occurrence of the inverse MNR in some of our intrinsic het-Si devices. The explanation is based on the band alignment of the constituent phases of nanocrystalline domains embedded in an amorphous matrix, and is derived from the model given by Lucovsky and Overhof that described and explained the inverse MNR in heavily doped microcrystalline silicon.…”
Section: H Meiling A) and R E I Schropp B)mentioning
confidence: 82%
“…13 Cross-sectional transmission electron microscopy ͑TEM͒ images show that this heterogeneous material consists of crystallites which are embedded in an amorphous phase. 14,15 These heterogeneous structures offer significant advantages over conventional plasmaenhanced CVD-based ͑PECVD͒ a-Si:H TFTs. First, the HWCVD het-Si TFTs do not show any shift of the threshold voltage upon prolonged gate voltage stress, in contrast to the conventional a-Si:H TFTs.…”
Section: H Meiling A) and R E I Schropp B)mentioning
confidence: 99%
“…The threshold voltage does not shift upon prolonged application of a gate-voltage. It has been suggested that not only the H content but rather the H bonding structure is responsible for the difference in metastable character for PECVD and HWCVD layers [94,96,97,625].…”
Section: Xib2 Stabilitymentioning
confidence: 99%
“…The silicon film crystalline fraction was determined from Raman spectroscopy. Measured spectra were deconvoluted into the characteristic crystalline (520 cm -1 ) and amorphous (480 cm -1 ) peaks and the ratio of their areas used to compute the ratio of crystalline to amorphous silicon [25,26]. The films were also characterized by XRD, to determine the grain size and preferred orientation.…”
Section: Hot-wire Deposited Si Filmsmentioning
confidence: 99%